Fuel Consumption of Tubular Lamp and Led Lamp in Generator Set On Laboratory Scale - Abid Mohamad Arif; Adi Susanto; Ririn Irnawati (Jurnal Perikanan dan Kelautan, 2015)
Utilization of light as artificial attractant has grown rapidly since electric lamp discovered. The use of energy saving lamp is one way to reduce operation costs, because almost all of the energy from generator is used to turn on the lights. The research aimed to analyze distribution of light illumination and fuel consumption of tubular lamp and LED lamp that can be used by fishermen in fishing operations. This study use 12.5 watts LED lamp and 24 watts tubular lamp each 5 pieces. Measurement of light illumination with a cover and without cover was conducted at distance 1 meter from the light source starts from the angle 0°-180° with angle 10° of intervals. Fuel consumption testing performed for 1 hour with 5 times repetition. The highest of light illumination of LED lamp without cover is 189 lux at angle 0°, while the tubular lamp is 152 lux at angle 40°. The highest of light illumination of LED lamp with cover is 236 lux at angle 0° and 10°, while the tubular lamp is 223 lux at angle 0°. Fuel consumption of LED lamp have average 405.16 ml for one hour, while 514.78 ml for tubular lamp. The average of electrical power was spent to turn on 5 LED lamp is 46.7 watts, while for 5 tubular lamp is 106.8 watts.